Sokrates og oss: Et essay om Sokrates’ forsvarstale, tekstfortolkning og filosofihistorie - Anfinsen, Roar (Nordlit, 2014)
Socrates and Us: An Essay on the Apology of Socrates, Philological Interpretations and History of Philosophy. I start out with a philological problem, the question of how to translate a disputed passage (30b 2–4) in Plato’s Apology. This problem is connected to a philosophical question, the Socratic and Platonic opinion on the relation between virtue, material goods and happiness. I then discuss the role of our «pre-understanding» in the interpretation of historical texts. Is a «purely» historical interpretation possible? Is a «purely» historical reading of philosophical texts worthwhile, if it does not concern our modern philosophical problems? In discussing these hermenutical questions I use John Stuart Mill’s reading of Plato as an example. A peculiar problem in the history of philosophy is the question of the historical Socrates and the different roles he has played. I investigate especially Mill’s use of the character of Socrates, but I also include examples from the twentieth century. Furthermore, I analyze Plato’s staging of Socrates in the Apology as a moral hero and the mythological status he is given. Finally, I discuss whether the Socratic philosophy is of any value today. I argue that the Socratic method ought to have an important place in moral and political education, and that this method is not value-neutral. It presupposes certain virtues, virtues taught and incarnated by the historical Socrates.